Interactive social robotic tutor - Tang, Jun Sheng. (2012)
In recent years, the education media have witnessed the birth of a new paradigm for learning environments: Social robotic tutors. Social robotic tutors are lifelike characters that are able to function like a real tutor, to create interactive, motivating and customizable learning environments. They open up exciting new possibilities for learning with robots as our present day learners expect learning not only to be a mere transfer of knowledge, but also a multi-directional social dialog with their educators. This report starts off by studying some of the learning trends and expectations of our present day learners, the effects of social interaction on learning, existing pedagogical agents in learning, some of the reasons why the Chinese language sees an increasing number of learners pursuing it, as well as the fundamentals of Hanyu Pinyin as a basic learning content. In subsequent parts of this report, a study was also done on the OPPR programming architecture that can suit a class of applications for implementation through the RIBML script. An experiment was also conducted to implement both the Hanyu Pinyin learning content and social interaction of the robot, in the form of a series of lessons. Feedback was gathered on how comprehensive the lessons delivered by a robotic tutor were, and if the amount of social interaction displayed by the robotic tutor was appropriate and sufficient. The results were positive and support that the social robotic tutor is an effective social tutoring media and that the social robotic tutor has the potential to be the next education media.